Análise da citotoxicidade e genotoxicidade do crack empregando o organismo-teste Perna perna - Ortega, Andressa dos Santos Barbosa [UNIFESP] (2018)
Crack cocaine is the main by-product of cocaine, being considered an epidemic drug in urban areas. Cocaine has been a target of recent studies, since its presence has been identified in aquatic matrices in different countries in low concentrations, but studies related to crack cocaine effects to the aquatic biota still scarce. From this perspective, the present study assessed the subletals effects of crack cocaine in the mussel Perna perna, which has a large occurrence in tropical and subtropical environments and it is used as a bioindicator in environmental monitoring programs. The adult mussels were exposed to an environmental concentration (0,5 µg.L-1) and concentration 10 and 100 times higher for 168 hours. Hemolymph, gills, digestive glands and adductor muscles were dissected every two days to be analyzed using a suite of biomarkers (Ethoxyresorufin O-deethylase (EROD), Dibenzylflurescein (DBF), Glutathione S-Transferase (GST), Glutathione Peroxidase (GPX), assess of lipid peroxidation (LPO), mitochondrial DNA damage (DNA strand break), cholinesterase (ChE) and assess the lysosomal stability (LMS). The significant increase of EROD and DBF activities was observed only in the gills. It was observed an increase of GST activity in gills, but it was observed a decrease of this activity in digestive glands. The antioxidant defenses measured by GPX were elevated only in the gills after two days of exposure. It was not observed lipid peroxidation, neither cholinesterase activity in any tissue, but it was observed mitochondrial DNA damage in gills and digestive glands. Alterations in LMS were observed in all crack cocaine concentrations. Our results demonstrated that the crack cocaine seems to be metabolized by CYP like and GST activities in gills, being able to generate oxygen-reactive species which increases the antioxidant activity and caused damage to DNA damage as well as to the lysosomal membrane of the mussel Perna perna.